A hybrid mathematical modeling strategy for controlling the mechanical performance of polyethylene/poly(ethylene-co-vinyl acetate)/Nanoclay cast films. (October 2019) - Ghasemi, Reza; Hemmati, Farkhondeh; Shadman, Alireza; Mohammadi-Roshandeh, Jamshid; Farizeh, Tara; Zandi, As'ad; Saeb, Mohammad Reza
Abstract: A two-stage mathematical modeling/optimization approach on the ground of response surface methodology (RSM) and desirability function (DF) was applied here to imitate and optimize the mechanical properties of polyethyelene (PE)/ethylene-vinyl acetate copolymer (EVA)/nanoclay (NC) nanocomposite cast films. First, a series of experiments were designed by the use of RSM so as to assess the effects of material parameters as well as processing temperature profile on the Young's modulus, tensile strength and strain at break of the nanocomposite films. Applying RSM statistical analysis, regression functions were examined and the best reduced interpolating functions were subsequently identified and transformed into the DF to optimize the desired responses concurrently. The findings unravelled that the PE/EVA/NC films with optimum elastic modulus, tensile strength and toughness are attainable by extruding the PE-rich blends at higher processing temperatures, preferably without the use of NC platelets. The multiple optimization strategies revealed the significance of the extruder temperature profile on mechanical properties as a key controlling factor governing the phase behavior of the PE/EVA blends. Highlights: A mathematical approach was proposed for fine-tuning the performance of PE/EVA/Nanoclay films. By hybridizing RSM and desirability function, a useful tool is provided for multi-objective optimization. The simultaneous optimization of all mechanical characteristics is of great importance from the industrial viewpoint. The optimal mechanical performance is attained for neat PE-rich blends extruded at higher barrel temperatures. The extruder temperature profile is of great significance for multiple optimization due to the phase behavior.